The role of an ecclesiastical network leader in a secular age : exploring missional leadership of transgenerational churches that reach dechurched and unchurched people with the gospel of Jesus Christ - Kapusinski, Russ (Russell) (St. Louis, Missouri : Covenant Theological Seminary, 2022)
1 electronic resource (1 PDF (x, 202 leaves)); Typescript; Abstract; Thesis (D. Min.)--Covenant Theological Seminary, 2022; Bibliography: leaves 197-202